What Do Buddhists Believe? - Morris, Tony (London Granta Books, 2006)
The teachings of Buddhism are varied, and it has a developed philosophical and mystical dimension; but at its core is a set of propositions and practices designed to meet the concerns of ordinary people: how to live a compassionate, creative, wise and, happy life. This work explores Buddhism's appeal, and gives an insight into its beliefs.
Include Index and Glossary
Keywords: Religious life--Buddhism -- Buddhism--Customs and practices -- Buddhism--Doctrines